2022
DOI: 10.3390/ph15121493
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds as Non-Nucleoside Inhibitors of Zika Virus Polymerase through Integration of In Silico and In Vitro Approaches

Abstract: Although the past epidemic of Zika virus (ZIKV) resulted in severe neurological consequences for infected infants and adults, there are still no approved drugs to treat ZIKV infection. In this study, we applied computational approaches to screen an in-house database of 77 natural and semi-synthetic compounds against ZIKV NS5 RNA-dependent RNA-polymerase (NS5 RdRp), an essential protein for viral RNA elongation during the replication process. For this purpose, we integrated computational approaches such as bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 89 publications
(168 reference statements)
0
2
1
Order By: Relevance
“…These scores were negatively correlated with the reference native ligand. Previous studies with similar in silico approaches on ZIKV-RdRp showed inhibitor compounds with docking scores ranging from −6.13 kcal/mol to −9.20 kcal/mol, which was higher than the top twelve selected compounds in this study [37][38][39]. The docking score of the native ligand was lower than the selected ligand, which suggested a higher strength of binding, but the docking program is a rigid protocol, and, thus, it has limitations in finding the optimum minimum energy state.…”
Section: Virtual Screening and Mm/gbsa (∆G Binding Free Energy)contrasting
confidence: 53%
“…These scores were negatively correlated with the reference native ligand. Previous studies with similar in silico approaches on ZIKV-RdRp showed inhibitor compounds with docking scores ranging from −6.13 kcal/mol to −9.20 kcal/mol, which was higher than the top twelve selected compounds in this study [37][38][39]. The docking score of the native ligand was lower than the selected ligand, which suggested a higher strength of binding, but the docking program is a rigid protocol, and, thus, it has limitations in finding the optimum minimum energy state.…”
Section: Virtual Screening and Mm/gbsa (∆G Binding Free Energy)contrasting
confidence: 53%
“…Likewise, Singh et al 264 used DockThor to study and evaluate molecules obtained from experimental GC–MS‐screening of crude plant extracts with virtual screening and characterize potential targets. Silva Ramos et al 265 used the DockThor approach to identify potent candidate molecules as inhibitors for the Zika virus NS5 RNA‐dependent RNA‐polymerase.…”
Section: Applicationsmentioning
confidence: 99%
“…Recently, many mechanisms of the antiviral action of QUER were described against several RNA and DNA viruses, including severe acute respiratory syndrome coronavirus 2 [ 5 , 8 , 13 , 19 , 20 ], and other ones were proposed through the integration of in silico approaches [ 13 , 21 ]. Therefore, in this study, we evaluated the antiviral activity of QUER on JUNV multiplication in different cell culture systems at different stages of the viral replication cycle, as well as the direct virucidal activity.…”
Section: Introductionmentioning
confidence: 99%